Development of independent curriculum-based technical drawing teaching materials at vocational high school - Budiyanto; Nurul Burhan, Nurul Burhan; Saian Nur Fajri, Saian Nur Fajri; Catur Rina Ajiningsih, Catur Rina Ajiningsih (Jurnal Taman Vokasi, 2024)
This research aims to develop teaching materials for Light Vehicle Engineering Skills Competency Vocational School students. This research uses the Research and Development (R&D) method which refers to the Borg and Gall design. The steps taken include needs studies, planning, initial field tests, main product field tests, and final product field tests. Improvements are made to each test. The results of the research are in the form of teaching materials containing technical drawing material. Teaching materials were developed referring to the independent curriculum. This teaching material was created to make it easier for class X vocational school students to study technical drawing material independently. The feasibility of teaching materials is based on the results of expert tests, initial field tests, main product field tests, and final product field tests. Teaching materials are said to be suitable if they meet the minimum good criteria for all aspects. The implications of this research are as follows: 1) technical drawing teaching materials developed based on the independent curriculum are able to increase students' interest in learning activities. 2) the existence of technical drawing teaching materials can help teachers in teaching and learning activities, teachers also do not need to repeat the material explained to students, and are able to improve the teacher's ability to manage the class, so that the teaching and learning process can run well, smoothly and effectively.